SGLT-2 Inhibitors and DPP-4 Inhibitors as Second-Line Drugs in Patients with Type 2 Diabetes: A Meta-Analysis of Randomized Clinical Trials - Wang, Keke; Zhang, Yansong; Zhao, Chunyang; Jiang, Mingyan (Hormone and Metabolic Research, 2018)
Sodium-glucose co-transporter 2 (SGLT-2) inhibitors and dipeptidyl peptidase 4 (DPP-4) inhibitors are both novel and second-line therapies in type 2 diabetes mellitus, yet no well-rounded comparison of these two drugs has been published. Upon searching randomized controlled trials in databases from inception to July 2018, we collected studies on the efficacy or safety of SGLT-2 inhibitors compared with those of DPP-4 inhibitors for the treatment of type 2 diabetes mellitus. A total of 12 randomized controlled studies including 4342 patients were included in this meta-analysis. Compared with DPP-4 inhibitors, SGLT-2 inhibitors achieved greater reductions in HbA1c (SMD –0.22; 95% CI: –0.30, –0.14; p=0.000) and fasting plasma glucose (SMD –0.48; 95% CI: –0.56, –0.41; p=0.000). In addition, these reductions increased with a prolonged treatment duration from 12 to 78 weeks. Geographically, significant reductions of SGLT-2 inhibitors in HbA1c and FPG were found in North America and Europe, but not in Asia. Furthermore, SGLT-2 inhibitors showed greater reductions in body weight (SMD −0.72; 95% CI: –0.81, –0.63; p=0.000) from baseline, with an increased incidence of genital infections (OR 4.49; 95% CI: 2.96, 6.83; p=0.000) and pollakiuria (OR 2.24; 95% CI: 1.05, 4.79; p=0.037) and a decreased incidence of hypertension and hyperglycemia. Overall, the current meta-analysis demonstrated that compared to DPP-4 inhibitors, SGLT-2 inhibitors have beneficial effects on HbA1c, FPG, body weight, SBP, DBP, and HDL-cholesterol in patients with type 2 diabetes. However, SGLT-2 inhibitors are associated with increased total cholesterol and LDL-cholesterol and a higher incidence of genital infections and pollakiuria.
Keywords: SGLT-2 inhibitors; DPP-4 inhibitors; type 2 diabetes mellitus; meta-analysis